The Effectiveness of Video Project Assignment on Students’ Speaking skill in SMP - Muhammad A'inul Haq; Niken Ayu Agustina (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
The purpose of this study is: (1) To measure the effectiveness of video project assignment on student’s‟ speaking skill at SMP YPI Darussalam 1 Cerme. In this study, researchers used a quantitative method approach with a type of Pre-Experimental research with the design of One Group Pretest Posttest. The research population includes 7th Grade at SMP YPI Darussalam 1 Cerme. With a total of 25 Students. Data collection techniques used are pretest and posttest sheets to determine the effect of use Video Project Assignment on the Learning Speaking Skill. Pretest and Posttest results data are then analyzed by conducting a Prerequisite Test which includes the Normality Test. The result of the research shows that the difference in the speaking skill between the student taught using English Video Project Assignment and those taught not using English Video Project Assignment is significant. By calculations (to = 8.75) and the size “t” listed in the value table t (tt.ts.5% = 2.06 and tt.ts.1% = 2.80 ). Then it can be known that the to is greater than the tt : 2,06<8,75>2,80